2023
DOI: 10.20944/preprints202303.0444.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Matrix Receptor CD44 Is Present in Astrocytes Throughout the Human CNS and Accumulates in Hypoxia and Seizures

Abstract: In the mammalian isocortex CD44, a cell surface receptor for extracellular matrix molecules, is present in pial-based and fibrous astrocytes of white matter, but not the protoplasmic astrocytes. In the hominid isocortex, CD44+ astrocytes comprise the subpial “interlaminar” astrocytes, sending long processes into the cortex. The hippocampus also contains similar astrocytes. We have examined all levels of the human CNS and found CD44+ astrocytes in every region. Astrocytes in white matter and astrocytes that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This association was observed across different tumors, where TNC expression correlated with areas of GW-like states and decreased proliferation (Figure S7B). We observed the expression of other notable genes such as CD44 and GAP43 along our latent time axis (Figure 6E); both of these genes, together with TNC, have been previously associated with MES1 Neftel subtype, but are also expressed by astrocytes and reactive astrocytes [57][58][59] . We observed a layered structured defined by GAP43, CD44, TNC, and VEGFA, where TNC region corresponded to the layer found between CD44/GAP43 and VEGFA (highest hypoxia) (Figure 6I-III.b).…”
Section: Ii)mentioning
confidence: 81%
“…This association was observed across different tumors, where TNC expression correlated with areas of GW-like states and decreased proliferation (Figure S7B). We observed the expression of other notable genes such as CD44 and GAP43 along our latent time axis (Figure 6E); both of these genes, together with TNC, have been previously associated with MES1 Neftel subtype, but are also expressed by astrocytes and reactive astrocytes [57][58][59] . We observed a layered structured defined by GAP43, CD44, TNC, and VEGFA, where TNC region corresponded to the layer found between CD44/GAP43 and VEGFA (highest hypoxia) (Figure 6I-III.b).…”
Section: Ii)mentioning
confidence: 81%
“…Astrocytes play roles in PD 99 . We and others have shown that astrocytes can be distinguished by CD44 expression into fibrous-like and protoplasmic 100 . We assigned astrocytic nuclei to a protoplasmic or fibrous-like sublineage and conducted DGE analysis ( Fig.…”
Section: Resultsmentioning
confidence: 77%
“…We then examined evidence for a transition from protoplasmic to fibrous-like states in PD, as we have seen in HD, hypoxia, and seizures 36,100 , using pseudotime analysis which is a means to order cells along a trajectory of gene signature. We ordered cells on the axis of variation along the genes that differ between the two astrocyte sublineages ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is important that such structures be maintained, dysfunctional PNNs are associated with neurodegenerative disorders (Li et al., 2024; Li, Li, et al., 2023). CD44 is also widely expressed by astrocytes throughout the CNS (Al‐Dalahmah et al., 2024) and its expression levels are elevated in hypoxic conditions and in migratory cells in glioblastoma (Inoue et al., 2023). CD44 is a multifunctional molecule that promotes the invasion and proliferation of tumor cells via a number of signaling pathways.…”
Section: The Cell‐associated Proteoglycans Of the Cns/pnsmentioning
confidence: 99%